Development Diagnostics for the Southern Cone - Eduardo Borensztein; Sebastián Miller; Gabriel Sánchez; Patricio Valenzuela (Inter-American Development Bank (IDB), 2014)
This is an update and revision of our 2009 study. Using a broad dataset and an original methodology, this paper reports composite development gaps across economic, social and institutional sectors. We define development gap as the distance between the observed and the expected development level of a country. The gaps are indicators of areas where development needs are bigger. Although we estimate the development gaps for all countries with available data, we focus the analysis of our results in five Southern Cone countries: Argentina, Brazil, Chile, Paraguay and Uruguay.
hdl:11319/6494
Keywords: O10; O160; O54; 330